Caracterizaçãoda alfa-manosidase produzida por Trichoderma harzianum durante o micoparasitismo - Mota, Paulo Roberto da (2015)
Fungi of the genus Trichoderma have emerged as biological control agents, especially those belonging to the species Trichoderma harzianum with various mechanisms involved include production of antibiotics, mycoparasitism, competition for nutrients and host plant resistance induction. Mycoparasitism is a sequential process that involves recognition of the host contact, adhesion, expression of specific genes and secretion of secondary metabolites. Several hydrolytic enzymes are involved in this process among them chitinases, beta-glucanases and proteases. Recent studies of T. harzianum interaction with some pathogens have shown that other enzymes may also be involved in this mechanism, among which alphamannosidase. Alpha-mannosidase has an essential role in the recycling of glycoproteins in filamentous fungi, but little is known about the role of these enzymes in mycoparasitism. This study aims to characterize the expression of T. alphamannosidase gene harzianum after growth in cell wall of Sclerotinia sclerotiorum (SS), Fusarium solani (FS) and Fusarium oxysporum (FO) as well as during the interaction in vivo . It was used as a control cell wall T. harzianum (TH). Also, jobs obtaining mutants of this gene in T. harzianum were performed. Our data show that alpha-mannosidase gene was highly expressed as T. harzianum grown in the presence of cell wall SS (4.5X), FS (18X) and FO (75X) compared to the control TH (1X). In comparison situation it was noticed a 75X greater expression in TH x FO state during contact as compared with the control (TH x TH). In other situations of confrontation did not observe a significant increase in expression. The promoter region, the selection mark and the terminator region of the alpha-mannosidase of T. harzianum gene was cloned into the pRS426 vector, and the deletion cassette was assembled by the recombination technique in Saccharomyces cerevisiae. Then, these vectors were used for transformation of T. harzianum and transformants were obtained by selection on plates containing hygromycin b. Approximately 50 transformants were obtained, but none of the alpha-mannosidase gene was successfully deleted. Obtaining more transformants is necessary for us to have a mutant alpha-mannosidase gene deleted.